ANALISIS PELUANG PENERBITAN OBLIGASI DAERAH SEBAGAI ALTERNATIF PEMBIAYAAN DAERAH - Dewi Okta; David Kaluge (Journal of Indonesian Applied Economics, 2011)
Municipal  bonds may  be used  as  a  source of  regional  funding.This  study aims  toanalyze the feasibility of issuing municipal bonds as an alternative source of financ-ing local infrastructure and analyze the strategies to be implemented by the govern-ment in the issuance of local bonds. Analysis tools used in this study were descriptivestatistics and SWOT analysis. The analysis showed that municipal bonds are an alter-native worth considering as a source of financing funding than other areas.Keywords: municipal bonds, the financing area, the SWOT.